Implementasi Visi Ternate Andalan (Mandiri Dan Berkeadilan) Dalam Meningkatkan SDM Di Kota Ternate (Studi Kasus Pada Sekretariat Daerah Kota Ternate) - Naufaldi Hadyan Saleh; Rahmat A Sabuhari; Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
This study aims to analyze the Implementation of the Mainstay Ternate Vision (Independence and Justice) in Improving Human Resources in the City of Ternate. This research is a qualitative research. There were 4 research informants at the Regional Secretariat of the City of Ternate. Case study research approach. Data collection techniques are carried out by observation, in-depth interviews and documentation. Based on the results of the study, it was found that: (1) The role of implementing the mainstay of Ternate's vision (self-sufficiency and justice) in improving existing human resources in Ternate City has not been fully understood by ASN or the community, this can be seen from several obstacles and factual results in the field that have not yet been implemented. according to what was said. (2) Professional ASN development priority program as described in Ternate's mainstay priority program has been carried out in accordance with the planned program, (3) Implementation of City development as an information center and strengthening of goods/services as outlined in Ternate's mainstay priority program continues to be pursued by encouraging Ternate to become smart city, preparing human resources to be educated in the field of goods and services. Improving supporting infrastructure at the entrance to the City of Ternate and building telecommunications infrastructure.